ULTRA HIGH TEMPERATURE-METAMORPHISM AND ITS SIGNIFICANCE IN THE CENTRAL INDIAN TECTONIC ZONE - Bhowmik S.K. (My University, 2006)
In the present study from the southern margin of the Central Indian Tectonic Zone, it is demonstrated how the metamorphic P-T path of ultrahigh-temperature granulite terranes can be reconstructed using the metamorphic transition in corundum granulites from early biotite melting to later FMAS solid-solid reaction. The extreme metamorphism in these rocks caused two-stage biotite melting, resulting in initial porphyroblastic garnet1 and later sapphirine-spinel1 incongruent solid mineral assemblages. During this process, the leucocratic and melanocratic layers in the corundum granulites evolved from an initial silica-oversaturated to a later silica-undersaturated domain. In the melanocratic layer, this allowed localized concentration of sapphirine-spinel1 and residual sillimanite1, producing an extremely restitic assemblage, at the culmination of peak metamorphism, BM1. BM1 is constrained at ~ 1000 °C at relatively deep crustal levels (P ~ 9 kbar) from the stability of ferroaugite in a co-metamorphosed Iron Formation granulite. During subsequent metamorphism (BM2), the reaction path and history in the corundum granulites shifted to the restitic domain allowing reacting sapphirine, spinel1 and sillimanite to produce coronal garnet2-corundum assemblage via a FMAS univariant reaction. In the final stages of reaction history, biotite2-sillimanite2-spinel2 assemblage was produced after garnet2-corundum due to localized melt-crystal interaction. The metamorphic sequence, when interpreted with the help of a newly constructed, qualitative KFMASH petrogenetic grid, reveals successive stages of heating, increasing pressure and cooling around the KFMASH invariant point, [Opx,Crd], which is consistent with a counterclockwise metamorphic P-T path. The near isobaric nature of post-peak cooling (ΔT ~ 250-300 °C) is also evident from multistage pyroxene exsolution and by the appearance of lamellar and coronal garnets in the Iron Formation granulites. This study provides the first tight constraint for ultrahigh-T metamorphism along a counter clockwise P-T trajectory in the Central Indian Tectonic zone, and has important bearing for terrane correlations in this part of East Gondwanaland. In addition, the new KFMASH grid allows evaluation of metamorphic phase relations in ultrahigh-T, corundum-bearing and corundum-absent aluminous granulites. © 2006 Elsevier B.V. All rights reserved.
Keywords: CENTRAL INDIAN TECTONIC ZONE; CORUNDUM GRANULITE; KFMASH GRID; UHT METAMORPHISM